ANALISIS LAPORAN KEUANGAN DENGAN MENGGUNAKAN METODE DU PONT DI PT. PERKEBUNAN NUSANTARA III (PERSERO) MEDAN - Ismail Nasution (Universitas Islam Islam Sumatera Utara, 2019)
The purpose of this study was to determine the financial performance of PT. Perkebunan Nusantara III (Persero) Medan in 2015 to 2017 using Du Pont's analysis.By using the Du Pont analysis method, it can find out: 1) the development of Net Profit Margin from 2015-2017, 2) the development of Total Asset Turn Over from 2015-2017, 3) the development of Return on Investment from 2015-2017. The analysis of Du Pont System analyzes health which includes the level of efficiency of asset use and measuring the level of profit on the sale of products produced by PT. Perkeunan Nusantara III (Persero) Medan.Financial performance of PT. Perkebunan Nusantara III (Persero) Medan, which is measured by ROI analysis using the Du Pont System method, is still not good. This can be seen from the assessment of the Du Pont System elements, namely NPM which is not efficient for three years, namely 2015 with 33% NPM, TATO 0.40 times, ROI 13.2%, 2016 NPM 15%, TATO 0, 13 times, ROI of 1.95%, 2017 results of NPM 20%, TATO 0.12 times, ROI of 2.4%. And the ROI value that always goes up and down where the value of ROI in 2016 has decreased from the value of 2015, then in 2017 has increased.